2000
DOI: 10.1111/j.1540-8159.2000.tb00963.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Multicenter Study on the Safety of a Pacemaker with Automatic Energy Control: Influence of the Electrical Factor on Chronic Stimulation Threshold.

Abstract: The effectiveness and safety of a pacemaker with automatic control of capture was evaluated in 162 patients followed at 27 Spanish centers. The aim of our prospective, multicenter, and randomized trial was to determine the relationship between the voltage output of the pulse generator and the stimulation threshold. We randomized 162 patients (107 men, mean age 75 +/- 12 years). We implanted a ventricular pacemaker model Regency SR+ or SC+ with Pacesetter's low polarization bipolar leads Membrane E 1450. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…Importantly, we did not observe the erroneously high thresholds that are sometimes seen in the evoked potential methods. These could be very bothersome in CRT devices by causing both diminished longevity and the possibility of phrenic nerve stimulation 6 . The data on the variability of the LV threshold supports the need for capture management and in that there are a significant number of patients with a high degree of threshold variation.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Importantly, we did not observe the erroneously high thresholds that are sometimes seen in the evoked potential methods. These could be very bothersome in CRT devices by causing both diminished longevity and the possibility of phrenic nerve stimulation 6 . The data on the variability of the LV threshold supports the need for capture management and in that there are a significant number of patients with a high degree of threshold variation.…”
Section: Discussionmentioning
confidence: 63%
“…These could be very bothersome in CRT devices by causing both diminished longevity and the possibility of phrenic nerve stimulation. 6 The data on the variability of the LV threshold supports the need for capture management and in that there are a significant number of patients with a high degree of threshold variation. New CRT-D systems include this ability to automatically measure the LV capture threshold.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Automatic pacing threshold algorithms have been demonstrated to be safe and useful for prolonging device longevity. [7][8][9] It should be noted that an automatic capture algorithm that examines an evoked response on a beat-to-beat basis would have prevented the adverse clinical outcome described in this case report. However, examples have been reported where these algorithms led to adverse clinical outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…Alternative methods shown to be effective in reducing polarization include coating of the lead with titanium nitride or iridium oxide, thereby increasing the lead/tissue interface surface area and reducing polarization, 14 and separation of the pacing and sensing vectors. 18 Both of these methods restrict the leads compatible with the feature to low polarization leads, [23][24][25] or bipolar leads, respectively. The LV Ring →Can vector investigated in this study demonstrated the feasibility of a modification to the methodology published by Butter et al 18 In contrast to the methodology published by Butter et al, the LV Ring →Can sensing vector shared the Can electrode between the pacing and sensing vectors during LV unipolar pacing in this study.…”
Section: Effect Of Polarization On the Evoked Responsementioning
confidence: 99%